Mycoplankton Biome Structure and Assemblage Processes Differ Along a Transect From the Elbe River Down to the River Plume and the Adjacent Marine Waters - Yang, Yanyan; Banos, Stefanos; Gerdts, Gunnar; Wichels, Antje; Reich, Marlis (Frontiers in Microbiology, 2021)
Rivers are transport systems and supply adjacent ecosystems with nutrients. They also serve human well-being, for example as a source of food. Microorganismic biodiversity is an important parameter for the ecological balance of river ecosystems. Despite the knowledge that fungi are key players in freshwater nutrient cycling and food webs, data on planktonic fungi of streams with higher stream order is scarce. This study aims to fill this knowledge gap by a fungi-specific 18S rRNA gene tag sequencing approach, investigating mycoplankton diversity in the Elbe River along a transect from shallow freshwater, to the estuary and river plume down to the adjacent marine waters (sections of 7th stream order number). Using multivariate analyses and the Quantitative Process Estimates (QPE) method, the questions of how mycoplankton communities as part of the river continuum change along the transect, what factors, spatial and environmental, play a role, and what assembly processes, such as selection or dispersion, operate along the transect were addressed. The partitioning of mycoplankton communities into three significant distant biomes was mainly driven by local environmental conditions that were partly under spatial control. The assembly processes underlying the biomes also differed significantly. Thus, variable selection dominated the upstream sections, while undominated processes like ecological drift dominated the sections close to the river mouth and beyond. Dispersal played a minor role. The results suggest that the ecological versatility of the mycoplankton communities changes along the transect as response for example to a drastic change from an autotrophic to a heterotrophic system caused by an abrupt increase in the river depth. Furthermore, a significant salinity-dependent occurrence of diverse basal fungal groups was observed, with no clade found exclusively in marine waters. These results provide an important framework to help understand patterns of riverine mycoplankton communities and serve as basis for a further in-depth work, so that fungi as an important ecological organism group can be integrated into models of e.g. usage-balance considerations of rivers.